Konsep Distribusi Berdasarkan Pemikiran Baqir As-Shadr dan Muhammad Abdul Mannan serta Penerapannya di Indonesia - Ade Syafitri; Hendra Hendra (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this research is to conduct an analysis on the concept of distribution in accordance with the thoughts of Muhammad Abdul Mannan and also Baqir As-Shadr. In this study, researchers use qualitative methods with the approach taken is a historical approach. As well as using literature study techniques. Distribution is an important part of an economy, especially in the country's development efforts. In it there are also aspects of ownership, justice and human resources that play an important role in the running of a country's economy. . Muhammad Abdul Mannan and Baqir al-Shadr have different views on the limitations of natural resources, the status of individual and state ownership and the fair distribution of opinions.